Vapor pressure of aqueous methyldiethanolamine mixed with ionic liquids - Ahmady, Afshin; Shamiri, Ahmad; Hashim, Mohd Ali; Aroua, Mohamed Kheireddine (Elsevier, 2013)
Vapor pressure of aqueous methyldiethanolamine (MDEA) mixed with various concentrations of 1-butyl-3-methyl-imidazolium tetrafluoroborate ([bmim][BF4]) and 1-butyl-3-methyl-imidazoliumdicyanamide ([bmim][DCA]) have been measured and compared with conventional solvents.